„Nawracam się nie dla katolików, ale na katolicyzm” (Sigrid Undset). Literacko-medialny wizerunek norweskiego konwertyty - Królczyk Bremer, Józefa (Studia Europaea Gnesnensia, 2015)
In the paper, the author attempts to reconstruct the image of a Catholic convert as conveyed in Norwegian media. The text first reconsiders the historical factors which affected the presence of Catholicism in Norway (Christianisation, Reformation, ban on Catholic religious practices, and the change of laws granting freedom of denomination). Subsequently, the author discusses several instances of famous Norwegian converts, including writer and Nobel prize winner Sigrid Undset, and reconstructs the social and intellectual climate which accompanied conversions in the interwar years. The article shows the specificity of Norwegian Catholicism, which consists in an exceptionally high share of people with university degrees and members of the Norwegian intellectual elite among the converts. Taking into account these particular conditions, the author describes the singular social climate and media coverage which surrounds the conversions. słowa klucze